2021
DOI: 10.1186/s12995-021-00329-9
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour and weight development of European and Asian seafarers during stay on board and at home

Abstract: Background Food choices on board merchant ships are limited and seafarers repeatedly described as being at high risk of developing overweight compared to the general population. Up to date, research has not distinguished whether seafarers gain weight on board or at home and whether eating habits differ in both settings. Methods As part of the e-healthy ship project, cross-sectional data were collected in two different measurements. In the first inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The remaining 35 full-text articles were evaluated. Among the 35 full-text papers reviewed, 21 studies with 145,913 study participants met the eligibility criteria and were included in the meta-analysis [ 9 , 10 , 17 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Figure 1 shows the entire process of finding, selecting, and including studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 35 full-text articles were evaluated. Among the 35 full-text papers reviewed, 21 studies with 145,913 study participants met the eligibility criteria and were included in the meta-analysis [ 9 , 10 , 17 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Figure 1 shows the entire process of finding, selecting, and including studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, twelve studies reporting the overweight prevalence with a total of 136,710 participants were selected for the meta-analysis [ 10 , 17 , 37 , 38 , 41 , 42 , 44 , 46 , 48 , 51 , 53 , 54 ]. In selected studies, the prevalence of overweight varied from 28.09% [ 42 ] to 51.51% [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it should also be considered that, for example, an increased BMI (which in our collective was >30 on average) is also associated with short sleep periods, as studies showed a consistent relationship between short sleep duration and higher total energy as well as fat intake [ 40 ]. In a study by Neumann et al [ 41 ], 43.9% of seafarers stated that they had gained weight since practicing this profession. Therefore, the codependence of lifestyle and sleep parameters should also be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Shipping companies, seafarers, and maritime medical doctors will develop, and pilot test the "Green Ship" health promotion for all on board. The German e-healthy ship is an example of an inspiring new-thinking in this area [50,51,53]. Health promotion protocols for hypertension and diabetes with non-pharmacological and/or pharmacological management will be developed.…”
Section: Preventive Interventionsmentioning
confidence: 99%